Pengaruh Antara Hypnobirthing, Yoga dan Senam Hamil Terhadap Tingkat Kecemasan Ibu Hamil Trimester III Di BPM Griya Bunda Ceria Palembang Tahun 2020 - Zelpina Herlinda Yanti; Satra Yunola; Putu Lusita Nati Indriani (Universitas Batanghari Jambi, 2021)
Trimester III is the period of pregnancy which is calculated from the gestational age of the 28th week to the 40th week. Psychological changes in pregnant women are estimated to occur 80%. third trimester. The purpose of this study was to examine the effect of hypnobirthing, yoga and pregnancy exercise on the anxiety level of third trimester pregnant women at BPM Griya Bunda Ceria in 2020. Research method: quantitative research, using the shapiro wilt test method with pre-test and post-test approaches. in this study were all third trimester pregnant women who checked their pregnancy at BPM Griya Bunda Ceria Palembang. Sampling using purposive sampling technique. Data collection was carried out by means of observation using a questionnaire sheet. The results: obtained from a total of 15 respondents. Based on the results of the Shapiro Wilt test, the p-Value is 0.05 where >α = 0.05 means that there is a significant influence between before and after hypnobirthing is done.statistically, the p-Value is 0,000, meaning that there is a significant effect between before and after yoga. Thus the hypothesis which states that there is an effect of yoga on the anxiety level of pregnant women in the third trimester which is statistically proven based on the paired shapiro wilt test, the p-Value is 0.00 in yoga, p-Value is 0.00 in pregnancy exercise, and the statistical test results are said to be related if the value The calculated p-Value <= 0.05 then Ho is rejected, meaning that it is significant, so the conclusion is that the two variables have a relationship, on the contrary, if the calculated p-Value> = 0.05, then Ho is accepted, meaning that the two variables have no significant relationship.